Exploring the genomic diversity and antimicrobial susceptibility of Bifidobacterium pseudocatenulatum in a Vietnamese population - Chung The, H; Nguyen Ngoc Minh, C; Tran Thi Hong, C; Nguyen Thi Nguyen, T; Pike, LJ; Zellmer, C; Pham Duc, T; Tran, T-A; Ha Thanh, T; Van, MP; Thwaites, GE; Rabaa, MA; et al. (American Society for Microbiology, 2021)
Bifidobacterium pseudocatenulatum is a member of the human gut microbiota, and specific variants of B. pseudocatenulatum have been associated with health benefits such as improving gut integrity and reducing inflammatory responses. Here, we aimed to assess the genomic diversity and predicted metabolic profiles of B. pseudocatenulatum cells found colonizing the gut of healthy Vietnamese adults and children. We found that the population of B. pseudocatenulatum from each individual was distinct and highly diverse, with intraclonal variation attributed largely to a gain or loss of carbohydrate-utilizing enzymes. The B. pseudocatenulatum genomes were enriched with glycosyl hydrolases predicted to target plant-based nondigestible carbohydrates (GH13, GH43) but not host-derived glycans. Notably, the exopolysaccharide biosynthesis region from organisms isolated from healthy children showed extensive genetic diversity and was subject to a high degree of genetic modification. Antimicrobial susceptibility profiling revealed that the Vietnamese B. pseudocatenulatum cells were uniformly susceptible to beta-lactams but exhibited variable resistance to azithromycin, tetracycline, ciprofloxacin, and metronidazole. The genomic presence of ermX and tet variants conferred resistance against azithromycin and tetracycline, respectively; ciprofloxacin resistance was associated with a mutation(s) in the quinolone resistance-determining region (GyrA, S115, and/or D119). Our work provides the first detailed genomic and antimicrobial resistance characterization of B. pseudocatenulatum found in the Vietnamese population, which can be exploited for the rational design of probiotics. IMPORTANCE Bifidobacterium pseudocatenulatum is a beneficial member of the human gut microbiota. The organism can modulate inflammation and has probiotic potential, but its characteristics are largely strain dependent and associated with distinct genomic and biochemical features. Population-specific beneficial microbes represent a promising avenue for the development of potential probiotics, as they may exhibit a more suitable profile in the target population. This study investigates the underexplored diversity of B. pseudocatenulatum in Vietnam and provides more understanding of its genomic diversity, metabolic potential, and antimicrobial susceptibility. Such data from indigenous populations are essential for selecting probiotic candidates that can be accelerated into further preclinical and clinical investigations.